Drinking Carling Out of Stella Glasses: People and Place in the Missing Middle - McEwan, Kathryn (Frontiers in Sociology, 2021)
As trends of social and economic change allow precarity to inch into the lives of those who may have been more accustomed to security (Standing, 2011, 2014), this paper will address the response of some young people who are caught 'betwixt and between' in potentially liminal states (Turner, 1967). Those whose families have undertaken intra- or inter-generational social mobility and who have made a home in a place, Ingleby Barwick in Teesside, that seems to be of them and for them- an in-between place that is seen as 'not quite' middle or working class. This paper draws data from a research project which adopted a qualitative phenomenological approach, to uncover the meaning of experiences for participants. Methods included focus groups and semi-structured interviews through which 70 local people contributed their thoughts, hopes, concerns and stories about their lives now and what they aspire to for the future. Places such as the large private housing estate in the North East of England on which this research was carried out, make up significant sections of the UK population, yet tend to be under-studied populations, often missed by a sociological gaze attracted to extremes. It was anticipated that in Ingleby Barwick, where social mobility allows access to this relatively exclusive estate, notions of individualism and deservingness that underlie meritocratic ideology (Littler, 2018; Mendick et al., 2015) would be significant, a supposition borne out in the findings. ‘Making it’ to Ingleby was, and continues to be, indicative to many of meritocratic success, making it ‘a moral place for moral people’ (McEwan, 2018). Consequently, the threat then posed by economic precarity, of restricting access to the transitions and lifestyles which create the 'distinction' (Bourdieu, 1984) required to denote fit to this place, was noted to be very real in a place ironically marked by many outside it as fundamentally unreal.